ANALISIS KOMPETENSI SAFETY COMMUNICATION PETUGAS KESELAMATAN DAN KESEHATAN KERJA (K3) KONSTRUKSI PT. X KOTA SEMARANG - Youlan Septiani; Baju Widjasena; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The construction sector contributed for the highest number of accidents in Indonesia. One of the preventive assessment to minimize the risk of accidents is safety communication. PT. X has a number of projects in Central Java, one of which is the building project Y located in the Semarang City. Number of staff and employees were about 220 people with the total number of safety officer were 3. In building projects Y still found accident figures, the use of PPE was not complete, the installation of safety sign were incomplete, and safety communication programs was not routinely performed. Construction safety officers must have competency of communication according to the Ministry of Manpower and Transmigration Republic of Indonesia Number 307 Year 2013. This study aimed to identify and analyze competency of safety communication of construction safety officer in PT. X Semarang City. This research was a descriptive qualitative in-depth interviews and observation. Subjects of this study amounted to 11 people, with 3 people as key informants and 8 as triangulation informant. The results showed that safety officer PT. X has met 60% performance criteria in implementing the competence elements of effective two-way communication in the framework of the implementation of OSH in the workplace, safety officer PT. X not meet all performance criteria within the competence element OSH enterprise management system communicates to the relevant parties, safety officer PT. X has met 75% of performance criteria in competence elements coordination and communication with relevant parties. Safety officer must conduct more stringent monitoring so that workers do not violate the OSH rules in the workplace.